A Need Analysis of ESP For Nursing Science Students at Stik Bina Husada Palembang - Agus Wahyudi; Pamuji, Arief; Ririn Martuti; Hapradespa, Aden (ITScience (Information Technology and Science), 2024)
The English language skills are also a determinant factor in the process of global knowledge exchange in various fields, including health, science, and technology. The connection between student needs and inadequate teaching approaches emphasizes the urgency of reforming English curricula in higher education. Identifying students’ needs in learning English is an important step in designing more effective and relevant curriculum and teaching methods. At STIK Bina Husada Palembang, English learning discusses the integration of four basic English language skills, namely speaking, listening, reading, and writing including aspects of grammar and vocabulary into the scope of nursing services and work both in clinical/community practice and in classroom and/or laboratory learning. In English language learning, need analysis helps educators design a curriculum that is appropriate to students' learning needs. By understanding these needs, teachers can develop relevant materials and target the language skills that are most useful to students in a particular context, such as academic, business, or everyday English. In this study, 150 students of the Nursing Science study program at STIK Bina Husada Palembang participated in the 2024/2025 academic year, but only 149 students filled out the Google form completely. The instrument used is a questionnaire that focuses on personal information, English language proficiency, and English language goals. The result showed that English language programs have been introduced early, and many university students still face challenges in communicating and understanding English, especially in public speaking, academic essay writing, and comprehending scientific articles. Low confidence and limited vocabulary are the main obstacles.